LATEST HELCIONELLOID MOLLUSCS FROM THE LOWER ORDOVICIAN OF KAZAKHSTAN - Gubanov A.P.; Peel J.S. (My University, 2001)
The helcionelloid mollusc Chuiliella elenae gen. et sp. nov. is described from the Lower Ordovician of Kazakhstan. It represents the geologically youngest record of a group of mainly bilaterally symmetrical ancient molluscs which originated in the earliest Cambrian, flourished during the early–mid Cambrian and was thought to have become extinct during the late Cambrian. Chuiliella is a typical helcionelloid in terms of shell shape, although the comarginal ornamentation characteristic of many helcionelloids is lacking. Interpretation of the raised margin of the aperture adjacent to the earlier coiled whorl as exhalant channels favours reconstruction of helcionelloids as endogastrically coiled, i.e., with the apex posterior.
Keywords: Ordovician; Helcionelloid Molluscs; Kazakhstan; Paleozoic::Ordovician; Палеозой::Ордовикская